Probing Saudi Arabia’s Literary Complexity: Combining Global and Local Narratives for a Hybrid National Literature - Ali M. Alshhre (Asiatic: IIUM Journal of English Language and Literature, 2023)
The article highlights the crucial need to balance Western and Saudi cultural themes in literature, specifically by incorporating the Saudi cultural heritage in a well-balanced manner. To explore this issue further, the article examines the impact of translated European literature on two influential Saudi female writers – Badriyyah al-Bishr and Raja Alem – and how they integrate Occidental literary themes into their works. It aims to explore the process of hybridisation by addressing three key points: the entry of world literature into Saudi Arabia, female writers’ employment of diverse themes from translated works, and the positive or negative consequences of this hybridisation. It will also propose solutions to mitigate possible negative effects. To assess the extent of this influence, a brief analysis of Al-Bishr’s Hend and the Soldiers and Alem’s The Dove’s Necklace is necessary to examine the impact of European literature on their works. The study highlights the potential of Saudi Arabian writers, particularly female ones, to serve as a medium for embedding and transferring “original themes” not only to Saudi Arabian audiences but also to Arab and international audiences. Despite the limited research on this subject in both Arabic and English, the study emphasises the critical importance of maintaining a well-balanced depiction of cultural elements in literature to preserve the unique cultural identity of Saudi Arabian national literature. The article suggests a balanced approach to incorporating themes from other cultures into Saudi literature, making them accessible to a wider audience, instead of criticising their adoption.